2015
DOI: 10.1515/ap-2015-0094
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of cystic echinococcosis: First record of G7 in Egypt and G1 in Yemen

Abstract: Few molecular studies have identified the current status of cystic echinococcosis in Egypt. The present study aimed to ascertain the genotype(s) of Echinococcus granulosus responsible for human hydatidosis in different Egyptian governorates (regions). Animal isolates were collected from 40 camels, 5 pigs and 44 sheep. 27 human isolates were included in the present study. Specific PCR was performed and followed by DNA sequencing for mitochondrial 12S ribosomal RNA gene and BLAST analysis.The sheep cysts were no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 21 publications
2
15
0
Order By: Relevance
“…Parasitic disease is a disease that seriously endangers the development of the camel industry (18,20,22,24) and that not only impedes the growth and development of camels (14,17,19), but is also one of the important reasons for the peak in camel deaths in the spring, resulting in great economic losses (15,16,21). What is more, many zoonotic parasites (1,9,10,12,13,28) could contaminate camel milk (18) and meat, posing potential threats to food safety and the health of the majority of herders (9,21,22). The documents on camel parasitic diseases in Iran showed that 48 helminth species were detected in the digestive system (21).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Parasitic disease is a disease that seriously endangers the development of the camel industry (18,20,22,24) and that not only impedes the growth and development of camels (14,17,19), but is also one of the important reasons for the peak in camel deaths in the spring, resulting in great economic losses (15,16,21). What is more, many zoonotic parasites (1,9,10,12,13,28) could contaminate camel milk (18) and meat, posing potential threats to food safety and the health of the majority of herders (9,21,22). The documents on camel parasitic diseases in Iran showed that 48 helminth species were detected in the digestive system (21).…”
Section: Discussionmentioning
confidence: 99%
“…Gastrointestinal parasites are one of the most common pathogens, and can not only lead to nutritional and immune inadequacy as well as stunted growth and delayed development (4)(5)(6)(7)(8)23), but also have adverse effects on the quality of camel meat and milk (18,21). These consequences of parasitical infection are potential threats to food safety and the health of the majority of herders (1,9,12,13,27,28). In recent years, with the rapid development of the Chinese camel breeding industry in the Tianshan Mountains pastoral area, the number of animals has reached more than 40,000.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3. Global distribution of the genotypes of Echinococcus canadensis and Echinococcus granulosus sensu stricto, based on molecular identification including areas of confirmed sympatry for E. ortleppi (Alam-Eldin et al, 2015;Alvarez Rojas et al, 2014;Cardona and Carmena, 2013;Carmera and Cardona, 2014;Casulli et al, 2010;Dybicz et al, 2013Dybicz et al, , 2015Farhadi et al, 2015;Guarnera et al, 2004;Hailemariam et al, 2012;Hüttner et al, 2009;Ito et al, 2013Ito et al, , 2014Jabbar et al, 2011;Jenkins et al, 2011Jenkins et al, , 2013Kędra et al, 1999Kędra et al, , 2000Konyaev et al, 2013;Lavikainen, 2005;Lavikainen et al, 2003Lavikainen et al, , 2006Lymbery et al, 2015;Mbaya et al, 2014;Mogoye et al, 2013;Moks et al, 2006;Monteiro et al, 2014;Moro et al, 2009;Nakao et al, 2007Nakao et al, , 2013bNakao et al, , 2015Oksanen and Lavikainen, 2015;Omer et al, 2010;Oudni-M'rad et al, 2016;Rinaldi et al, 2014;Rodriguez-Prado et al, 2014;Romig et al, 2015;Saarma et al, 2009;Schneider et al, 2010;Schurer et al, 2013Schurer et al, , 2014…”
Section: Pathology and Epidemiology Of Ce Highlight The Need For A DImentioning
confidence: 99%
“…In another record G7 genotype (pig strain) was detected in two human isolates and one pig isolate in Egypt, while G1 genotype (sheep strain) was detected in one human isolate from Yemen and in no animal isolates. This was the first record of G7 in Egypt and G1 in Yemen [32] .…”
Section: Discussionmentioning
confidence: 75%